Pelatihan Pembuatan Kepiting Presto Crispy Sebagai Diversifikasi Produk Pangan Berbasis Potensi Pesisir Di Kawasan Ekowisata Bagek Kembar, Sekotong - Wastu Ayu Diamahesa; Bagus Dwi Hari Setyono; Muhammad Baiul Hak; Fariq Azhar; Yesica Marcelina Romauli Sinaga; Zaenal Abidin; Laily Fitriani Mulyani; Yuliana Asri; Sahrul Alim; Dewi Putri Lestari (Universitas Mataram, 2026)
Abstract: Coastal areas have considerable potential to support community-based food product innovation, particularly through the utilization of local fishery resources. This community service activity aimed to improve the knowledge and practical skills of POKDARWIS Bagek Kembar in processing crab into a value-added food product, namely crispy pressure-cooked crab. The activity was carried out in Bagek Kembar Ecotourism Area, Cendi Manik Village, Sekotong District, West Lombok Regency, West Nusa Tenggara, from July to September 2025. The program involved preliminary identification, partner needs assessment, counseling, demonstration, and hands-on training. A total of 15 participants joined the training. The material covered raw material preparation, crab cleaning, basic food hygiene, pressure-cooking technique, seasoning, flour coating, and frying process to produce a crispy texture. The results showed that the participants were actively involved in discussions and practical sessions and were able to follow the main stages of crispy pressure-cooked crab processing. This activity introduced a simple and applicable processing technique that can potentially support local culinary diversification in the ecotourism area. Further assistance is needed, particularly in product standardization, food safety, packaging, marketing, and business feasibility analysis.